Game of Thrones House of the Dragon Season 1 Disc 3 - DeGrate, Charmaine; Sapochnik, Miguel; Sapochnik, Miguel; Kilner, Clare; Considine, Paddy; Smith, Matt, 1982-; Ifans, Rhys, 1967-; Frankel, Fabian; Home Box Office (Firm); Warner Bros. Entertainment; Studio Distribution Services (Firm) (Burbank, California Warner Bros. Entertainment, 2022)
Season one, disc three; episodes 5 and 6.
The reign of House Targaryen begins. House of the Dragon, the prequel to Game of Thrones, is based on George R.R. Martin's Fire & Blood. The series, which is set 200 years before the events of Game of Thrones, tells the story of House Targaryen.
We light the way -- The princess and the queen.
Title from container.
Originally broadcast on the HBO network as single episodes of a television program in 2021.
Paddy Considine, Matt Smith, Rhys Ifans, Fabien Frankel, Graham McTavish, Gavin Spokes, Bill Paterson, Steve Toussaint, Eve Best, Matthew Needham, Olivia Cooke, Emma D'arcy, Milly Alcock, Emily Carey.
Rating: Not rated CHV rating: 18A.
DVD, region 1, wide screen; Dolby digital 5.1.
English, French or Spanish dialogue; French or Spanish subtitles; subtitled for the deaf and hard of hearing (SDH).
Keywords: Martin, George R. R. -- Television adaptations; Targaryen, House of -- (Fictitious family) -- Drama; Westeros (Imaginary place) -- Drama; Royal houses -- Drama; Action and adventure television programs; Drama; Fiction television programs; Television adaptations; Television programs; Television series; Video recordings for the hearing impaired